Juridicial Analysis on The Implementation of Fiduciary Collateral Execution in The Post-The Constituonal Court’s Ruling No. 18/PUU-XVII/2019 - Cut Nabilla Sarika; Sunarmi Sunarmi; Dedi Harianto; Rudy Haposan Siahaan (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
Fiduciary collateral as a type of collateral gives the rights of executorial to creditors to do parate execution on the object of fiduciary collateral when a debtor defaults. In practice, however, collateral misuses this right by seizing the collateral coercively and illegally. This becomes the basics for Judicial Review agains Article 15, paraghraphs 2 and 3 of Law No. 42/1999 on Fiduciary Collateral on January 6, 2020, and the Constitutional Court issued the Ruling No. 18/PUU-XVII/2019 which causes dispute in people. The research problems are whether the Constitutional Court’s Ruling is contrary to the collateral which gives easianess for the execution, how about the implementation of parate execution in the post – the Constituonal Court’s Ruling, and how about the legal consequence of debtor and creditor.The research use descriptive juridicial normative method. The data were gathered by conducting library research. The gathered data were analyzed qualitatively. The result of the analysis shows that Ruling does not impede the right of executing by creditors so that it is in accordance with the executorial right in fiduciary collateral, and creditors can still play their role in doing parate execution hen debitors default, on condition that debtors voluntarily hand in the fiduciary collateral. It may be difficult to do this in the foreclosure sale; therefore, it has to be certain in writing the clauses in the fiduciary contract. In this case, a Notary is required to add a clause about default in the contract and should refer to the Constituonal Court’s Ruling No. 18/PUU-XVII/2019 as the legal ground in writing fiduciary collateral contract.